Synthesis of homoisoflavonoids with a coumarin moiety and coumarin-pyrazole or coumarin-isoxazole hybrids based on them - Myshko, Nataliia; Mrug, Galyna; Bondarenko, Svetlana; Frasinyuk, Mihaylo (My University, 2022)
In this research in the oxa-Diels–Alder reaction of thermally generated ortho-quinone methides from 3-aryl-8-(N,N-dimethylaminomethyl)coumarines with (2E)-3-(N,N-dimethylamino)-1-(2-hydroxyphenyl)prop-2-en-1-ones and the subsequent cascade of reactions were obtained 8-[4-oxo-4H-chromen-3-yl)methyl]-7-hydroxy-3-phenyl-2H-chromen-2-ones. Synthesis of pyrazole-3-arylcoumarin hybrids was performed by recyclization of chromone core of homoisoflavonоids under hydrazine actions. Target isoxazoles were synthesized by the reaction of homoisoflavonоids with hydroxylamine hydrochloride in ethanol in presence of DBU

У цьому дослідженні в реакції окса-Дільса–Альдера термічно генерованих орто-хінон метидів з 3-арил-8-(N,N-диметиламінометил)кумаринів з (2E)-3-(N,N-диметиламіно)-1-(2 -гідроксифеніл)проп-2-ен-1-онами та подальшим каскадом реакцій було отримано 8-[4-оксо-4Н-хромен-3-іл)метил]-7-гідрокси-3-феніл-2Н-хромен-2-они. Синтез гібридів піразол–3-арилкумарину проводили рециклізацією хромонного ядра гомоїзофлавоноїдів під дією гідразину. Цільові ізоксазоли синтезовано реакцією гомоїзофлавоноїдів з гідроксиламіну гідрохлоридом в етанолі в присутності ДБУ
Keywords: homoisoflavonoid; сoumarin; oxa-Diels-Alder reaction; pyrazole; isoxazole; гомоізофлавоноїд; кумарин; реакція окса-Дільса-Альдера; піразол; ізоксазол; кафедра харчової хімії